Innovative Transformation of Manufacturing Vacuum Equipment at Mechanical Engineering Enterprises - N. N. Nurmukhametov; A. B. Amerkhanova; K. T. Auyezova (Экономика: стратегия и практика)
The purpose of the article investigates introducing new products processes at mechanical engineering enterprises based on the innovative transformation of vacuum production equipment. In the context of global competition activities of large Kazakhstan’s enterprises are characterized by an insufficient level of innovation activity. Building the infrastructure and production potential is the main in effective management production activities of engineering enterprises. The heads of enterprises are primarily concerned by the situation since innovation development has a significant impact on competitiveness, industrial enterprises’ export potential and could ensure the balance of the economic sectors. Authors are interested in conducting an economic analysis of the business entities’ activities, which aimed at efficiency increasing and quality of work in all links of industrial production. Authors suppose that practice requires the development of complex measures related to the peculiarities of investigating scientific and practical problems of increasing the production activities efficiency in the economy. In the authors’ opinion, the investment project can become the basis for effective innovation implementation at mechanical engineering enterprises. They analyzed the financial activity of the enterprise and developed measures to reduce the production costs and products sales on the example of JSC «Vostokmashzavod». The result of the study is an investment project that arouses interest from the subjects of the machine-building industry from the point of view of the practical applicability of projects to reduce production costs, and the efficiency of their management.